Improving Cognitive Development of Students by Reading Corner Program in Elementary School level - Maratul Qiftiyah (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2020)
Cognitive development is one of the most important children’s development experiences.  In essence, this potential is determined at the time of conception which is influenced by hereditary factors, but this cognitive potential can also develop depending on environmental factors and the maturity of the opportunity given to determine the maximum developmental limits at the level of intelligence.  Reading is one of the most important parts of every type of learning process.  Through reading, activities would get a lot of knowledge that can lead to success.  This research aims to describe the cognitive development of students through reading corners.  This type of research is field research, using a qualitative approach to the descriptive method.  The research was carried out at SDN 02 Nusa Bakti, South Sumatra province, Indonesia.  The research subjects are teachers and students.  The data were obtained from interviews and observations.  The results showed that a fun reading corner activity as an effort to implement literacy reading movements could develop cognitive abilities of students, including students doing assimilation, and accommodation processes to achieve equilibration, and students are more enthusiastic and motivated to increase their reading interest.